Rituals and Ethics: The Influence of Traditional Religious Practices on Christian Worship and Morality - Rotimi Alaba Oti (Journal of Research in Social Science and Humanities, 2025)
AbstractThis paper examines the intricate relationship between traditional religious rituals and their influence on Christian worship and ethical frameworks. It examines how pre-Christian and indigenous religious practices have shaped, complemented, or transformed Christian liturgical traditions and moral codes. By analysing historical, theological, and anthropological perspectives, the study reveals how ritual elements such as rites of passage, sacrificial offerings, festivals, and communal ceremonies have been integrated or adapted into Christian worship. The research also highlights the ethical implications of these integrations, focusing on how they inform concepts of morality, community cohesion, and spiritual discipline within Christian contexts. Furthermore, the article investigates the tension and dialogue between preserving traditional customs and adhering to Christian doctrinal purity. The research method involves oral interviews with Christian pastors, and case studies from cultural backgrounds and online sources are presented to illustrate the dynamic interplay between tradition and faith, showcasing how rituals can serve as vehicles for ethical instruction and spiritual reflection. The conclusion emphasises the ongoing evolution of Christian worship and ethics in response to cultural influences, advocating for a nuanced understanding of how tradition shapes contemporary Christian identity and moral practice. Involving ourselves with our cultures makes others benefit from them and become one in unity, wisdom and love.